EVALUASI STATUS KESUBURAN TANAH DI DESA BARU KECAMATAN BATANG KUIS - Arfansyah, Didik; Manurung, Hariani; Mubarak, Raihan Zaki; Baniray, Azra Al; Sakiah, Sakiah (Institute of Computer Science (IOCS), 2025)
Soil fertility is the ability of soil to support plants and provide nutrients for plants in a state of availability,enough, and balanced. Soil fertility is inseparable from the physical and chemical properties of soil.physical and chemical properties of the soil, both of which are interrelated with each other. This research aims to determine some of the physical and chemical properties of soil from Desa Baru, Batang Kuis Subdistrict.Kuis. Soil samples were taken compositely from two different depths depths, namely 0-20 cm and 20-40 cm. soil samples were tested in the laboratory of the Indonesian Institute of Palm Technology. Parameters testing parameters are soil texture, total pore space, bulk density, particle density, soil moisture content, soil pH, and C-Organic. soil moisture content, soil pH, and C-Organic. The results showed that the soil texture The soil texture is clay, pore space is 53.19% and 50%, bulk density is 1.13 gr/ml and 1.12 gr/ml, particle density is 2.418 gr/ml and 2.252 gr/ml. Moisture content in dry conditions were 8.96% and 7.525%, while at field capacity reached 33.33% and 35.13%. Soil pH was measured using the following methods comparison of soil and water, as well as soil and KCl. The results showed soil pH 5.3 and 5.3 in the ratio of 1:2.5 H2O, soil pH 3.9 and 3.8 in the ratio of soil and KCl 1:2.5 H2O. soil and KCl ratio of 1:2.5. The content of C-Organic value is 1.32% and 1.24%, soil organic matter is 2.28% and 2.15%. Based on the results of the study, soil fertility is low but still favorable for plant growth.favorable for plant growth.